Mosques on the Margins? Islamic Religious Spaces and Identities in Paris. (1st December 2006) - Chadwick, Kay
This article holds that mosques represent a central component in the negotiating and recognition of the permanent presence of Islam in France. It debates their locational obscurity and architectural invisibility, illustrative of a peripheral existence which sits uneasily alongside the faith's longstanding presence in France, and examines the challenges they represent for the principle of laïcité.